Self-medication and its associated factors in Amdanga block of West Bengal - Bhattacharyya, Suchetana; Mitra, Sayeli; Basu, Swagatendra Narayan; Alagesan, Inba Raja; Basu, Rivu (Indian Journal of Community Health, 2022)
Background: The WHO defines the use of medications without prior medical consultation regarding indication, dosage and duration of treatment as self-medication. The practice is a global problem. Aims and Objectives: The study was conducted to describe the care seeking behavior of rural self-medicators living in Amdanga Block of West Bengal and to assess the belief in medicines by the self-medicators. Material & Methods: A descriptive cross-sectional study was conducted by interviewing with a pretested semi-structured questionnaire on 665 self-medicators out of 1740 adults who were interviewed in 80 villages of Amdanga Block, West Bengal. A three-stage sampling method was used to reach the study population. A three month recall on self-medication practice was considered operationalizing the “pull” and “push” factors of self-medicators using a Pshycho-social framework. The variables were Socio-demographic factors, Care Seeking Behaviors, Health System related factors, Belief in Medicines according to the framework. Results: The prevalence of self-medication was found to be 38.2%. 63% of the study subjects were female and 56.3% had a literacy status of middle school and above. 54.4% relied on their old prescription for self-medication. 68.7% had an initial choice to consult a doctor but later self-medicated of whom 53.2% changed their choice due to monetary and transport issues while 38.5% thought of self-medication considering their disease was mild in nature. Conclusion: Awareness and health education can link rural subjects with primary care facility and right decisions on care can be provided.